1998
DOI: 10.1091/mbc.9.9.2375
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of 5S rRNA in Mammalian Mitochondria

Abstract: Mammalian mitochondrial ribosomes contain two prokaryotic-like rRNAs, 12S and 16S, both encoded by mitochondrial DNA. As opposed to cytosolic ribosomes, however, these ribosomes are not thought to contain 5S rRNA. For this reason, it has been unclear whether 5S rRNA, which can be detected in mitochondrial preparations, is an authentic organellar species imported from the cytosol or is merely a copurifying cytosol-derived contaminant. We now show that 5S rRNA is tightly associated with highly purified mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 43 publications
(55 reference statements)
2
74
0
2
Order By: Relevance
“…Mitochondria from these cells were isolated and gradient-purified as described previously (18). Briefly, cells were harvested by low speed centrifugation and resuspended in homogenization buffer (10 mM NaCl, 1.5 mM MgCl 2 , and 10 mM Tris-HCl, pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria from these cells were isolated and gradient-purified as described previously (18). Briefly, cells were harvested by low speed centrifugation and resuspended in homogenization buffer (10 mM NaCl, 1.5 mM MgCl 2 , and 10 mM Tris-HCl, pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in yeast have shown that DNA can leave the mitochondria at a rate of ∼2 × 10 −5 but no flow of DNA was detected in the opposite direction (Thorsness and Fox 1993). However, it is clear that the mitochondria of a wide range of eukaryotes, including humans, import various RNAs (Doersen et al 1985;Li et al 1994;Magalhaes et al 1998) and even viral RNA (Somasundaran et al 1994). …”
Section: Nuclear Pseudogenesmentioning
confidence: 99%
“…25,26 Schon and colleagues have recently reported that a 5S ribosomal RNA may be imported, but its function has yet to be determined. 27 It is therefore possible that mammalian mitochondria do not possess an efficient import mechanism for nucleic acids. Vestweber and Schatz, 28 however, were able to demonstrate that by subjecting import-competent, isolated mitochondria to DNA-conjugated mitochondrial precursor proteins, the DNA became nuclease or phosphodiesterase resistant, consistent with the mitochondria importing nucleic acids via the general protein import pathway.…”
Section: Mitochondrial Targeting and Importmentioning
confidence: 99%